Pengaruh Tingkat Kedisiplinan Dan Kelincahan Terhadap Kecerdasan Kinestetik Pada Permainan Futsal - Hudain, Muh Adnan; Sudiadharma, Sudiadharma; Hasan, Muh Said; Jamaluddin, Jamaluddin; Azizah, Fitriah (STAMINA, 2024)
The objectives of this study are to: (1) Analyze the effect of discipline level on kinesthetic intelligence in futsal players. (2) Evaluate the effect of agility on kinesthetic intelligence in futsal players. (3) Explore the interaction between the level of discipline and agility in influencing kinesthetic intelligence in futsal players. This research is an experimental research. The sample is a member of Futsal UPT SMAN 3 Pinrang, has experience participating in Futsal matches or competitions, and attendance in the training process. After using purposive sampling method, the sample size consisted of 63 students and all of them were male students. The research collection techniques used are questionnaire and observation methods while the instruments used include a questionnaire of discipline and kinesthetic intelligence consisting of indicators and question grids. The effect of discipline on kinesthetic intelligence in the UPT SMAN 3 Pinrang futsal game obtained a t value of 2.716> t table 1.997. The effect of agility on kinesthetic intelligence in futsal games at UPT SMAN 3 Pinrang obtained a t value of 10.721> t table 1.997. The effect of discipline and agility on kinesthetic intelligence in futsal games at UPT SMAN 3 Pinrang obtained F value of 57.793 > F table 4.0098. Based on the results of data analysis and discussion that has been done, it can be concluded that there is a significant influence between the level of discipline on kinesthetic intelligence in futsal games at UPT SMAN 3 Pinrang, there is a significant influence of agility on kinesthetic intelligence in futsal games at UPT SMAN 3 Pinrang, and there is an influence of the level of discipline and agility together on kinesthetic intelligence in futsal games at UPT SMAN 3 Pinrang.